2000
DOI: 10.1002/(sici)1098-108x(200004)27:3<310::aid-eat8>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of body image dimensions by race/ethnicity and gender in a university population

Abstract: Objective We examined affective and cognitive components of body image related to physical appearance, weight, and health among 120 university men and women of three racial/ethnic groups: African American, European American, and Latino/a American. Method Participants completed a Background Information Sheet, the Multidimensional Body‐Self Relations Questionnaire (MBSRQ), the Body‐Esteem Scale (BES) with additional items, and the Balanced Inventory of Desirable Responding (BIDR). We tested for effects of race/e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
78
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(92 citation statements)
references
References 20 publications
8
78
2
Order By: Relevance
“…However, the current and ideal figures selected by African Americans were larger than those selected by Caucasians. This is consistent with previous research suggesting that African Americans are more comfortable with a larger body size than are Caucasians (Gluck & Geliebter, 2002;Miller & Gleaves, 2000). Further, African Americans reported higher BMIs than did Caucasians, which is also consistent with previous research (Perry et al 2004).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the current and ideal figures selected by African Americans were larger than those selected by Caucasians. This is consistent with previous research suggesting that African Americans are more comfortable with a larger body size than are Caucasians (Gluck & Geliebter, 2002;Miller & Gleaves, 2000). Further, African Americans reported higher BMIs than did Caucasians, which is also consistent with previous research (Perry et al 2004).…”
Section: Discussionsupporting
confidence: 92%
“…Males, by contrast, appear to be generally satisfied with their overall body shape and size, although some may wish to be larger or more muscular (Peixoto-Labre, 2002;Stanford & McCabe, 2005). Additional studies have revealed that African Americans tend to report less body dissatisfaction than Caucasians, as well as a preference for a larger current figure and a larger ideal figure than Caucasians (Gluck & Geliebter, 2002;Miller & Gleaves, 2000). Further, when evaluating opposite sex body preferences, African American men find a larger female figure more attractive than do Caucasian men (Jackson & McGill, 1996;Thompson, Sargent, & Kemper, 1996).…”
mentioning
confidence: 99%
“…First, our sample consisted entirely of Caucasian individuals. As BMI, 12 -14 and possibly body image, 15,16 are known to differ by ethnic group, it would be unwise to apply these norms to non-Caucasian populations. Second, our BMI norms are based on self-reported height and weight.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns with body image and weight dissatisfaction have focused much of the research on eating disorders (Stanford & McCabe, 2002;Striegel-Moore & Smolak, 2000;Miller & Gleaves et al, 2000). Meanwhile other researchers have suggested that the more complex relationship between perceptions of self and those of the other sex add to increased body dissatisfaction and risk for eating disorders (Gleaves & Cepeda-Benito et al, 2000;Stanford & McCabe, 2002).…”
Section: Cultural Pressuresmentioning
confidence: 99%